Rating targeting and the confidence levels implicit in bank capital - Esa Jokivuolle; Samu Peura (Bank of Finland, 2006)
The solvency standards implicit in bank capital levels, as reported eg in Jackson et al (2002), are much higher than those required for top ratings, if standard single period economic capital models are taken seriously.We explain this excess capital puzzle by forward looking rating targeting behaviour by banks, which aims at maintaining rating above a minimum target in future periods.We calibrate to data on actual bank capital the confidence level used by the median US AA rated bank to maintain at least a single A rating.The calibrated confidence level is in line with the historical probability of an AA rated bank to be downgraded below A.
URN:NBN:fi:bof-20140807552
Keywords: G21; G32; 330; bank capital; credit rating; value-at-risk; economic capital; capital structure